Interação entre líquidos iônicos mono e dicatiônicos derivados do imidazolíneo e metilcelulose em solução aquosa e estado gel - Ziembowicz, Francieli Isa (2016)
This paper describes the interactions between methylcellulose (MC) with a serie of imidazolium ionic liquids (LIs) monocationic (CnMIMBr) and its similar dicationic (Cn(MIM)2Br2) in a aqueous enviroment. The effect of the alkyl chain's length (n = 10, 12, 14 e 16), the type and concentration of LIs (above and below of its critial micellar concentration (cmc)) were evaluated with the assistance of isothermal titration microcalorimetry techniques (ITC), electric conductivity, surface tension and dynamic light scattering (DLS). It was observed that the interactions are favored with the growth of the alkyl chain's length of the determinated LI, since the critical aggregation concentration (cac) and the difference of Gibbs energy (Δ ºPS) considerably decreases with the increase of LI hydrophobicity. Furthermore, the binding of the monocationic LIs is more effective in the methoxyl groups of MC when they are compared to the LIs dicationic. This result can be understood considering that the LIs Cn(MIM)2Br2 are bolaform molecules that contain two hydrophilic head groups connected by a hydrophobic hydrocarbon chain and therefore are more hydrophilic when compared with CnMIMBr. The effects of adding (CnMIMBr) and Cn(MIM)2Br2 in apparent viscosity and gelation of MC were studied by rheology and micro differential scanning calorimetric (Micro-DSC). The concentration of MC was kept constant at 15 g L-1 and the concentration of LIs was varied above and below the cmc. It was observed that the LIs affect the pattern of the sol-gel transition, the gelation temperature (salt-out effect below the cmc and effect salt-in, above the cmc), the gel strength and apparent viscosity of the MC solution. This behavior can be explained by the hydrophobic interaction between the MC and LIs, which depends on the concentration, of alkyl chain length and type of LI (conventional or bolaform). These mixtures MC/LI can act as viscosifying fluids, with potential applications in enhanced oil recovery.